RNA-seq and integrated network analysis reveals the hub genes and key pathway of paclitaxel inhibition on Adriamycin resistant diffuse large B cell lymphoma cells. Issue 3 (1st March 2022) - Hong, Haoyuan; Luo, Bin; Qin, Yingying; Li, Sizhu; Peng, Zhigang
ABSTRACT: About 40% of patients with diffuse large B-cell lymphoma (DLBCL) develop drug resistance after first-line chemotherapy, which remains a major cause of morbidity and mortality. The emergence of DLBCL drug resistance is mainly related to Adriamycin. Our previous research shows that Paclitaxel could be a potential therapeutic drug for the treatment of Adriamycin-resistant DLBCL. Based on the results of RNA-seq and integrated network analysis, we study the potential molecular mechanism of Paclitaxel in the treatment of Adriamycin-resistant DLBCL in multiple dimensions. A CCK-8 assay showed that the inhibitory effect of Paclitaxel on Pfeiffer and Pfeiffer/ADM (Adriamycin-resistant DLBCL cell lines) is significantly higher than that of Adriamycin ( P ＜ 0.05). Five hub genes (UBC, TSR1, WDR46, HSP90AA1, and NOP56) were obtained via network analysis from 971 differentially expressed genes (DEGs) based on the RNA-seq of Paclitaxel-intervened Pfeiffer/ADM. The results of the network function module analysis showed that the inhibition of Pfeiffer/ADM by Paclitaxel was closely related to ribosome biosynthesis in eukaryotes. The results of RT-qPCR showed that the mRNA levels of the five hub genes in the Pfeiffer/ADM group were significantly lower than those in the Pfeiffer group and the Pfeiffer/ADM Paclitaxel-treated group ( P ＜ 0.05). Consistent with studies, Paclitaxel exhibited a significant inhibitory effect on Adriamycin-resistant DLBCL, which may have played a role in the five hub genes (UBC, TSR1, WDR46, HSP90AA1 and NOP56) and ribosome biosynthesis in eukaryotes pathway, but the specific regulation needs further experimental verification.